Electrode foil for electrolytic capacitor, electrolytic capacitor, and method for producing electrolytic capacitor

By adopting a double-layer dielectric layer structure of the first metal and the second metal oxide in the electrolytic capacitor and forming a conductive polymer solid electrolytic layer on the second metal oxide dielectric layer, the problem of difficulty in achieving high capacity and good voltage withstand in the prior art is solved, and efficient and low-cost electrolytic capacitor production is achieved.

JP7660300B2Active Publication Date: 2025-04-11PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021550504
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-30
Filing Date
2020-09-04
Publication Date
2025-04-11
Estimated Expiration
2040-09-04

AI Technical Summary

Technical Problem

It is difficult for the prior art to achieve high capacity and good voltage withstand performance of electrolytic capacitors simultaneously.

Method used

A double-layer dielectric layer structure comprising a first metal and a second metal oxide is adopted, wherein the dielectric layer thickness (T1) of the first metal oxide is greater than the dielectric layer thickness (T2) of the second metal oxide, and a thin layer of conductive polymer solid electrolytic layer is formed on the second metal oxide dielectric layer.

Benefits of technology

The high capacity and good voltage withstand performance of the electrolytic capacitor are achieved, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660300000003
    Figure 0007660300000003
  • Figure 0007660300000004
    Figure 0007660300000004
  • Figure 0007660300000005
    Figure 0007660300000005
Patent Text Reader

Abstract

This electrode foil for an electrolytic capacitor comprises: a positive electrode body containing a first metal; a first dielectric layer which covers at least a portion of the positive electrode body and contains an oxide of the first metal; and a second dielectric layer which covers at least a portion of the first dielectric layer and contains an oxide of a second metal. The first metal includes at least one selected from the group consisting of titanium, tantalum, niobium, and aluminum, and the second metal includes at least one selected from the group consisting of silicon, zirconium, hafnium, and tantalum. By using the electrode foil for an electrolytic capacitor, in which the thickness T2 of the second dielectric layer is smaller than the thickness T1 of the first dielectric layer, an electrolytic capacitor having a large capacity and an excellent withstand voltage can be provided.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode foil for an electrolytic capacitor, an electrolytic capacitor, and a method for manufacturing an electrolytic capacitor. [Background technology]

[0002] Conventionally, in electrolytic capacitors, a substrate having a roughened surface and containing a valve metal is subjected to chemical conversion (anodization) to form a dielectric layer containing an oxide of the valve metal on the finely irregular surface of the substrate.

[0003] Meanwhile, Patent Document 1 proposes forming another dielectric layer on the dielectric layer, the dielectric layer containing an oxide of a valve metal different from the valve metal contained in the dielectric layer, and an additive such as carbon, in order to increase the capacitance and reduce leakage current. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-115475 A Summary of the Invention

[0005] However, the method of Patent Document 1 may not be able to simultaneously achieve an increase in capacity and an improvement in voltage resistance.

[0006] Books The invention 1. side Electrode foil for electrolytic capacitors The present invention relates to an anode body including a first metal, a first dielectric layer covering at least a portion of the anode body and including an oxide of the first metal, and a second dielectric layer covering at least a portion of the first dielectric layer and including an oxide of a second metal different from the first metal. do. The first metal includes at least one selected from the group consisting of titanium, tantalum, niobium, and aluminum, and the second metal includes at least one selected from the group consisting of silicon, zirconium, hafnium, and tantalum. Hmm. And,The thickness T2 of the second dielectric layer is smaller than the thickness T1 of the first dielectric layer. stomach.

[0007] The present invention Second Aspects Electrolytic capacitors related to teeth, Related to the first aspect an electrode foil; and a solid electrolyte layer covering at least a portion of the second dielectric layer of the electrode foil. do. The solid electrolyte layer includes a conductive polymer. nothing.

[0008] The present invention Third Aspects The method for manufacturing an electrolytic capacitor according to the present invention teeth, The method includes the following first and second steps. In the first step, A substrate containing a first metal is chemically converted to form a first dielectric layer containing an oxide of the first metal so as to cover at least a portion of the substrate. In the second step, A second dielectric layer containing an oxide of a second metal different from the first metal and having a thickness T2 smaller than the thickness T1 of the first dielectric layer is formed so as to cover at least a portion of the first dielectric layer, thereby obtaining an electrode foil. 。 The first metal includes at least one selected from the group consisting of titanium, tantalum, niobium, and aluminum, and the second metal includes at least one selected from the group consisting of silicon, zirconium, hafnium, and tantalum. nothing.

[0009] According to the present invention, an electrolytic capacitor having a large capacity and excellent voltage resistance can be obtained. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a schematic view of a surface portion of an electrode foil according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a perspective view that illustrates a schematic configuration of a wound body included in the electrolytic capacitor according to the embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view illustrating a schematic configuration of an electrolytic capacitor according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] [Electrode foil for electrolytic capacitors] The electrode foil for electrolytic capacitor according to the embodiment of the present invention includes an anode body including a first metal, a first dielectric layer covering at least a portion of the anode body and including an oxide of the first metal, and a second dielectric layer covering at least a portion of the first dielectric layer and including an oxide of a second metal different from the first metal. The first metal includes at least one selected from the group consisting of titanium (Ti), tantalum (Ta), niobium (Nb), and aluminum (Al). The second metal includes at least one selected from the group consisting of silicon (Si), zirconium (Zr), hafnium (Hf), and tantalum (Ta). The thickness T2 of the second dielectric layer is smaller than the thickness T1 of the first dielectric layer.

[0012] By covering at least a part of the first dielectric layer with the second dielectric layer, the voltage resistance of the electrolytic capacitor is improved. Furthermore, by making the thickness T2 of the second dielectric layer smaller than the thickness T1 of the first dielectric layer, a low-cost electrolytic capacitor with a large capacity can be obtained regardless of the dielectric constant of the second dielectric layer. By making the thickness T2 of the second dielectric layer smaller than the thickness T1 of the first dielectric layer, a well-balanced combination of excellent voltage resistance and high capacity can be obtained, resulting in an electrolytic capacitor with a large CV value, which will be described later.

[0013] When the first metal contains at least one selected from the group consisting of Ti, Ta, Nb, and Al, the first dielectric layer is easily formed by chemical conversion. From the viewpoint of being more advantageous in terms of cost, the first metal preferably contains Al. The oxide of the first metal (first dielectric layer) contains at least one selected from the group consisting of TiO2, Ta2O5, Nb2O5, and Al2O3. Forming such a first dielectric layer thick is advantageous for reducing the cost of the process.

[0014] The second metal includes at least one selected from the group consisting of Si, Zr, Hf, and Ta. In this case, it is easy to form a dense second dielectric layer with a uniform thickness by atomic layer deposition (ALD). From the viewpoint of easy formation of a second dielectric layer with high voltage resistance and small thickness, it is preferable that the second metal includes Si. From the viewpoint of increasing capacity, it is preferable that the second metal includes Hf. The oxide of the second metal (second dielectric layer) includes at least one selected from the group consisting of SiO2, ZrO2, HfO2, and Ta2O5. When the second dielectric layer includes two or more types of oxides of the second metal, the oxides may be mixed or may be arranged in layers. On the first dielectric layer Thin second metal oxide To form a film of This improves the voltage resistance of the electrolytic capacitor at low cost. It is preferable that the oxide of the second metal has a higher relative dielectric constant than the oxide of the first metal, since this is advantageous for increasing the capacity of the electrolytic capacitor.

[0015] The ratio T1 / T2 of the thickness T1 of the first dielectric layer to the thickness T2 of the second dielectric layer is preferably greater than 1 and equal to or less than 20. When T1 / T2 is equal to or less than 20, it is easy to improve the voltage resistance at low cost. From the viewpoint of a balance between cost reduction, high capacity, and voltage resistance, T1 / T2 is more preferably equal to or more than 1.25 and equal to or less than 10, and even more preferably equal to or more than 1.5 and equal to or less than 5.

[0016] The total thickness of the thickness T1 of the first dielectric layer and the thickness T2 of the second dielectric layer is, for example, 7 nm or more and 500 nm or less. From the viewpoint of increasing the capacity, it is preferable that the total thickness of T1 and T2 is small, for example, 7 nm or more and 12.5 nm or less, or 7 nm or more and 10.5 nm or less. When the dielectric layer is composed of the first dielectric layer and the second dielectric layer, the thickness of the dielectric layer can be made smaller than when the dielectric layer is composed of only the first dielectric layer, and the voltage resistance can be improved. The thickness T2 of the second dielectric layer is, for example, 0.5 nm or more and 250 nm or less.

[0017] The composition of the oxide of the first metal contained in the first dielectric layer and the oxide of the second metal contained in the second dielectric layer can be determined by elemental analysis using energy dispersive X-ray spectroscopy (EDX) on a cross-section of the electrode foil.

[0018] The thickness T1 of the first dielectric layer and the thickness T2 of the second dielectric layer are obtained by observing the cross section of the electrode foil using a scanning electron microscope (SEM) or a transmission electron microscope (TEM). Specifically, using a cross section image of the electrode foil obtained by SEM or TEM, the thickness of the first dielectric layer is measured at 10 arbitrary points, and the average value of these is obtained as the thickness T1. The thickness of the second dielectric layer is also measured at 10 arbitrary points, and the average value of these is obtained as the thickness T2.

[0019] An example of an electrode foil according to an embodiment of the present invention will now be described with reference to Fig. 1. Fig. 1 is a cross-sectional view that typically illustrates a surface portion of an electrode foil according to an embodiment of the present invention.

[0020] The electrode foil is an anode foil 10 including an anode body 110 containing a first metal and a dielectric layer 120 covering at least a portion of the anode body 110. The dielectric layer 120 includes a first dielectric layer 121 covering at least a portion of the anode body 110 and a second dielectric layer 122 covering at least a portion of the first dielectric layer 121. The first dielectric layer 121 includes an oxide of the first metal. The second dielectric layer 122 includes an oxide of a second metal different from the first metal. A thickness T2 of the second dielectric layer 122 is smaller than a thickness T1 of the first dielectric layer 121.

[0021] Anode body 110 is a metal foil containing a first metal and having a surface roughened by etching or the like, and has a core portion 111 and a porous portion 112. Porous portion 112 has a large number of pits P. First dielectric layer 121 is formed up to the surface of the deepest parts of pits P by chemical conversion of the metal foil. Second dielectric layer 122 is formed up to the surface of the deepest parts of pits P by the ALD method.

[0022] [Electrolytic capacitor] The electrolytic capacitor according to the embodiment of the present invention includes the above-mentioned electrode foil and a solid electrolyte layer that covers at least a part of the second dielectric layer of the above-mentioned electrode foil. The solid electrolyte layer includes a conductive polymer (π-conjugated polymer). The conductive polymer includes polypyrrole, polythiophene, polyaniline, and derivatives thereof.

[0023] The electrolytic capacitor may further include a solvent. The solvent preferably contains a glycol compound and / or a glycerin compound (hereinafter also referred to as glycol compound, etc.). The glycol compound, etc. may be contained in the electrolytic solution described below. When the solvent contains a glycol compound, etc., the orientation or crystallinity of the π-conjugated polymer contained in the solid electrolyte layer is enhanced. This improves the conductivity of the solid electrolyte layer and reduces the equivalent series resistance (ESR) of the electrolytic capacitor. In addition, the contact between the solid electrolyte layer and the second dielectric layer is improved, and the withstand voltage characteristics are improved.

[0024] The glycol compounds include ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, polyalkylene glycols having a molecular weight of about 190 to 400, etc. The glycerin compounds include glycerin, polyglycerin, etc. The degree of polymerization of polyglycerin is preferably 2 or more and 20 or less. The glycol compounds etc. may be used alone or in combination of two or more.

[0025] The electrolytic capacitor may further include an electrolytic solution. By using the electrolytic solution, an electrolytic capacitor having an excellent function of repairing the dielectric layer can be obtained. The electrolytic solution includes, for example, a solvent and an ionic substance (solute, for example, an organic salt) dissolved in the solvent.

[0026] The solvent may be an organic solvent or an ionic liquid. As the solvent, a high boiling point solvent is preferable. For example, carbonate compounds such as propylene carbonate, cyclic sulfones such as sulfolane, lactones such as γ-butyrolactone, amides such as N-methylacetamide, N,N-dimethylformamide, and N-methyl-2-pyrrolidone, esters such as methyl acetate, ethers such as 1,4-dioxane, ketones such as methyl ethyl ketone, formaldehyde, etc. can be used. The solvent may be used alone or in combination of two or more.

[0027] An organic salt is a salt in which at least one of an anion and a cation contains an organic substance. For example, trimethylamine maleate, triethylamine borodisalicylate, ethyldimethylamine phthalate, mono-1,2,3,4-tetramethylimidazolinium phthalate, mono-1,3-dimethyl-2-ethylimidazolinium phthalate, etc. may be used. One type of organic salt may be used alone, or two or more types may be used in combination.

[0028] The first dielectric layer is a chemical conversion film, and from the viewpoint of forming the second dielectric layer, it is preferable that the ratio T1 / R of the thickness T1 (nm) of the first dielectric layer to the chemical conversion rate R (nm / V) of the chemical conversion film and the rated voltage Vw (V) of the electrolytic capacitor satisfy the relationship (T1 / R) / Vw≦3. (T1 / R) / Vw is more preferably 2.5 or less, even more preferably 2.0 or less, and particularly preferably 1.5 or less. In this case, it is easy to adjust the thickness balance of the first dielectric layer and the second dielectric layer so that T1 / T2 is more than 1 and 20 or less, and it is easy to achieve a good balance of high voltage resistance, high capacity, and cost reduction. The chemical conversion rate R means the thickness (nm) of the chemical conversion film (layer of oxide of the first metal) formed per volt of the chemical conversion voltage Vf.

[0029] The formation rate R varies depending on the type of the first metal. For example, if the first metal is Al, the formation rate R is 1.4 nm / V (or higher) or 2.0 nm / V (or lower). Note that electrolytic capacitors with a rated voltage Vw of 10 V or less are considered to be "lower" products, and electrolytic capacitors with a rated voltage Vw of more than 10 V are considered to be "higher" products. If the first metal is Ta, the formation rate R is 2 nm / V.

[0030] [Manufacturing method of electrolytic capacitors] A method for manufacturing an electrolytic capacitor according to an embodiment of the present invention includes a first step of forming a first dielectric layer containing an oxide of the first metal by chemically converting a substrate containing a first metal so as to cover at least a part of the substrate, and a second step of forming a second dielectric layer containing an oxide of a second metal different from the first metal and having a thickness T2 smaller than the thickness T1 of the first dielectric layer so as to cover at least a part of the first dielectric layer, thereby obtaining an electrode foil. The first metal includes at least one selected from the group consisting of Ti, Ta, Nb, and Al. The second metal includes at least one selected from the group consisting of Si, Zr, Hf, and Ta. The electrode foil described above is obtained by the first and second steps. Each step will be described in detail below.

[0031] (1st step) A substrate containing a first metal is chemically converted to form a first dielectric layer containing an oxide of the first metal so as to cover at least a part of the substrate. A metal foil having a roughened surface is usually used for the substrate. The metal foil may be a foil of the first metal or an alloy foil containing the first metal. The thickness of the metal foil is not particularly limited, but is, for example, 15 μm or more and 300 μm or less. The roughening is performed by an etching process or the like. A plurality of pits are formed on the surface of the metal foil by the roughening. The first dielectric layer can be formed on the surface of the deepest part of the pits by chemical conversion of the metal foil.

[0032] In the first step, a chemical formation voltage Vf is applied to the substrate. The thickness T1 of the first dielectric layer changes depending on the chemical formation voltage Vf. From the viewpoint of forming the second dielectric layer, the ratio of the chemical formation voltage Vf to the rated voltage Vw of the electrolytic capacitor: Vf / Vw is preferably 3.0 or less, more preferably 2.5 or less, even more preferably 2.0 or less, and particularly preferably 1.5 or less. In this case, it is easy to adjust the thickness balance of the first dielectric layer and the second dielectric layer so that T1 / T2 is greater than 1 and less than 20, and it is easy to achieve a good balance between high voltage resistance, high capacity, and cost reduction.

[0033] The method for chemically converting the substrate is not particularly limited, and for example, the substrate is immersed in a chemical conversion solution such as an ammonium adipate solution, and a predetermined voltage Vf is applied thereto (anodic oxidation).

[0034] The diameter of the pits formed on the surface of the metal foil is not particularly limited, but is preferably 50 to 2000 nm in terms of increasing the surface area and facilitating the formation of the second dielectric layer deep into the pits. The diameter of the pits is the most frequent pore size in the pore distribution measured, for example, by a mercury porosimeter. The depth of the pits is also not particularly limited, and may be appropriately set according to the thickness of the metal foil. In particular, from the viewpoint of increasing the surface area and maintaining the strength of the electrode foil, the depth of the pits (thickness D of the etched region in which the pits are formed) is preferably 1 / 10 or more and 4 / 10 or less of the thickness of the metal foil before etching. The thickness D of the etched region is the average value of any 10 points in a cross-sectional image of the metal foil obtained by SEM or TEM.

[0035] (2nd process) In the second step, a second dielectric layer is formed so as to cover at least a part of the first dielectric layer, the second dielectric layer containing an oxide of a second metal different from the first metal and having a thickness T2 smaller than the thickness T1 of the first dielectric layer. In the second step, it is preferable to form the second dielectric layer so that the ratio T1 / T2 of the thickness T1 of the first dielectric layer to the thickness T2 of the second dielectric layer is greater than 1 and less than or equal to 20.

[0036] In the second step, the second dielectric layer is preferably formed by atomic layer deposition (ALD). The ALD method can form a second dielectric layer having a small and uniform thickness. In the ALD method, the variation in the thickness values ​​of the second dielectric layer measured at 10 points when determining the thickness T2 is small, and the standard deviation is, for example, 0.5 nm or less.

[0037] The ALD method is a film formation method in which a source gas containing a second metal and an oxidizing agent are alternately supplied to a reaction chamber in which an object is placed, to form a layer (second dielectric layer) containing an oxide of the second metal on the surface of the object. In the ALD method, the self-limiting action functions, so that the second metal is deposited on the surface of the object in atomic layers. Therefore, the thickness of the second dielectric layer is controlled by the number of cycles in which one cycle is the supply of source gas → exhaust (purge) of the source gas → supply of the oxidizing agent → exhaust (purge) of the oxidizing agent. In other words, the ALD method is a preferable method in that the thickness of the layer to be formed can be easily controlled. Furthermore, while the chemical vapor deposition (CVD) method is performed at a temperature condition of 400 to 900°C, the ALD method can be performed at a temperature condition of 100 to 400°C. In other words, the ALD method is also preferable in that it can suppress thermal damage to the metal foil.

[0038] In the ALD method, if the diameter of the pit is, for example, about 10 nm, a thin film can be formed on the surface of the deep part of the pit. As described above, the pit formed on the surface of the metal foil usually has a diameter of 50 nm or more. Therefore, the ALD method can form a second dielectric layer on the surface of the deep part of a pit with a small diameter and a large aspect ratio.

[0039] The oxidizing agent may be any oxidizing agent that has been used in the ALD method. Examples of the oxidizing agent include water, oxygen, ozone, etc. The oxidizing agent may be supplied to the reaction chamber as plasma using the oxidizing agent as a raw material.

[0040] The second metal is supplied to the reaction chamber by gasifying a precursor containing the second metal. The precursor is an organometallic compound containing the second metal, which makes it easier for the second metal to be chemically adsorbed to the target object. As the precursor, various organometallic compounds that have been used in the conventional ALD method can be used.

[0041] Examples of precursors containing Si include N-sec-butyl(trimethylsilyl)amine (CH 19 NSi), 1,3-diethyl-1,1,3,3-tetramethyldisilazane (CH 23 NSi2), 2,4,6,8,10-pentamethylcyclopentasiloxane ((CH3SiHO)5), pentamethyldisilane ((CH3)3SiSi(CH3)2H), tris(dimethylamino)silane ([(CH3)2N]3SiH), tris(isopropoxy)silanol ([(H3C)2CHO]3SiOH), chloropentanemethyldisilane ((CH3)3SiSi(CH3)2Cl), dichlorosilane (SiH2Cl2), tris(dimethylamino)silane ([(CH3)2N]3SiH), tris(isopropoxy)silanol ([(H3C)2CHO]3SiOH), Dimethylaminosilane (Si[N(CH3)2]4), tetraethylsilane (Si(C2H5)4), tetramethylsilane (Si(CH3)4), tetraethoxysilane (Si(OC2H5)4), dodecamethylcyclohexasilane ((Si(CH3)2)6), silicon tetrachloride (SiCl4), silicon tetrabromide (SiBr4), bis(ethylmethylamino)silane (H2Si[N(C2H5)(CH3)]2), bis(diethylamino)silane (H2Si[N(C2H5)2]2), bis ( Tertiary Butyl Amino ) Examples include silane (H2Si[NH(C4H9)]2).

[0042] Zr-containing precursors include, for example, bis(methyl-η 5cyclopentadienyl)methoxymethylzirconium (Zr(CH3C5H4)2CH3OCH3), tetrakis(dimethylamino)zirconium(IV) ([(CH3)2N]4Zr), tetrakis(ethylmethylamino)zirconium(IV) (Zr(NCH3C2H5)4), zirconium(IV) t-butoxide (Zr[OC(CH3)3]4), and the like.

[0043] Examples of precursors containing Hf include hafnium tetrachloride (HfCl4), tetrakis dimethylaminohafnium (Hf[N(CH3)2]4), tetrakis ethylmethylaminohafnium (Hf[N(C2H5)(CH3)]4), tetrakis diethylaminohafnium (Hf[N(C2H5)2]4), and hafnium t-butoxide (Hf[OC(CH3)3]4).

[0044] An example of a precursor containing Ta is tris(ethylmethylamido)(t-butylimido)tantalum(V). ( Examples include Ta(Nt-C4H9[N(C2H5)CH3]3), tantalum(V) ethoxide (Ta(OC2H5)5), tris(diethylamido)(t-butylimido)tantalum(V) ((CH3)3CNTa(N(C2H5)2)3), and pentakis(dimethylamino)tantalum(V) (Ta(N(CH3)2)5).

[0045] (3rd step) The method for producing an electrolytic capacitor may include a third step of forming a solid electrolyte layer containing a conductive polymer so as to cover at least a part of the second dielectric layer of the electrode foil. The solid electrolyte layer may be formed, for example, by chemically polymerizing and / or electrolytically polymerizing a raw material monomer on the second dielectric layer of the electrode foil. Alternatively, the solid electrolyte layer may be formed by applying a solution in which a conductive polymer is dissolved or a dispersion in which a conductive polymer is dispersed to the second dielectric layer of the electrode foil. After the third step (after the formation of the solid electrolyte layer), the electrode foil may be further impregnated with a solvent or an electrolytic solution.

[0046] When the anode body having a dielectric layer is an electrode foil (anode foil) as shown in Fig. 1, a wound body 100 as shown in Fig. 2 may be produced before the third step. Fig. 2 is a development view for explaining the configuration of the wound body 100.

[0047] When preparing the wound body 100, in addition to the anode foil 10, a cathode foil 20 is prepared. The cathode foil 20 may be a metal foil, similar to the anode foil 10. The type of metal constituting the cathode foil 20 is not particularly limited, but a valve metal such as Al, Ta, Nb, or an alloy containing a valve metal may be used. If necessary, the surface of the cathode foil 20 may be roughened.

[0048] Next, the anode foil 10 and the cathode foil 20 are wound with the separator 30 interposed therebetween. One end of the lead tab 50A or 50B is connected to the anode foil 10 and the cathode foil 20, respectively, and the lead tabs 50A and 50B are wound to form the wound body 100. The other ends of the lead tabs 50A and 50B are connected to lead wires 60A and 60B, respectively.

[0049] The separator 30 is not particularly limited, and for example, a nonwoven fabric containing cellulose, polyethylene terephthalate, vinylon, aramid fiber, or the like as a main component can be used.

[0050] Next, a stop tape 40 is placed on the outer surface of the cathode foil 20 located in the outermost layer of the wound body 100, and the end of the cathode foil 20 is fixed with the stop tape 40. When the anode foil 10 is prepared by cutting from a large foil, the wound body 100 may further be subjected to a chemical conversion treatment in order to provide a dielectric layer on the cut surface.

[0051] The wound body 100 is impregnated with a solution in which a conductive polymer is dissolved or a dispersion liquid in which a conductive polymer is dispersed, to form a solid electrolyte layer between the anode foil 10 and the cathode foil 20. After the formation of the solid electrolyte layer, the wound body 100 may be further impregnated with a solvent or an electrolytic solution. Examples of a method for impregnating the wound body 100 with a solution or the like contained in a container include a method of immersing the wound body 100 in a solution or the like contained in a container, and a method of dripping the solution or the like onto the wound body 100. The impregnation may be performed in an atmosphere under reduced pressure, for example, 10 kPa to 100 kPa, preferably 40 kPa to 100 kPa.

[0052] Next, the wound body 100 is sealed to obtain the electrolytic capacitor 200 as shown in Fig. 3. To manufacture the electrolytic capacitor 200, first, the wound body 100 is housed in the bottomed case 211 so that the lead wires 60A, 60B are located on the opening side of the bottomed case 211. The material of the bottomed case 211 can be a metal such as aluminum, stainless steel, copper, iron, brass, or an alloy of these metals.

[0053] Next, the sealing member 212, which is formed so that the lead wires 60A and 60B pass through, is placed above the wound body 100, and the wound body 100 is sealed in the bottomed case 211. The sealing member 212 may be made of any insulating material, and is preferably made of an elastic material. Among these, silicone rubber, fluororubber, ethylene propylene rubber, and hypalon, which have high heat resistance, are preferred. (trademark) Rubber, butyl rubber, isoprene rubber, and the like are preferred.

[0054] Next, a horizontal drawing process is performed near the open end of bottomed case 211, and the open end is curled by crimping it to sealing member 212. Finally, sealing is completed by placing seat plate 213 on the curled portion. Thereafter, an aging process may be performed while applying a rated voltage.

[0055] In the above embodiment, a wound-type electrolytic capacitor has been described, but the scope of application of the present invention is not limited to the above, and the present invention can also be applied to other electrolytic capacitors, for example, stacked-type electrolytic capacitors.

[0056] [Example] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.

[0057] Example 1 A wound electrolytic capacitor (Φ (diameter) 6.3 mm × L (length) 9.9 mm) was fabricated with a rated voltage Vw of 2.0 V. A specific method for manufacturing the electrolytic capacitor will be described below.

[0058] (Preparation of anode foil) An Al foil with a thickness of 120 μm was prepared. This Al foil was subjected to a direct current etching process to roughen the surface. An etched region with a thickness of 40 μm was formed on the surface of the Al foil, and the pit diameter was 100 to 200 nm.

[0059] The roughened surface of the Al foil was subjected to chemical conversion treatment to form a first dielectric layer so as to cover the finely uneven surface of the Al foil. The chemical conversion treatment was performed by immersing the Al foil in an ammonium adipate solution and applying a chemical conversion voltage Vf to the Al foil. The chemical conversion voltage Vf was set to 5.0 V, and the Vf / Vw ratio was set to 2.5.

[0060] Next, a second dielectric layer was formed to cover the first dielectric layer by the ALD method (temperature: 300°C, precursor: tridimethylaminosilane, oxidant: O3, pressure: 1 Pa, 30 cycles). In this way, an anode body (anode foil) having the first dielectric layer and the second dielectric layer in this order on its surface was obtained. The anode foil was then cut to a specified size.

[0061] EDX analysis confirmed that the second dielectric layer was a layer of SiO2 and the first dielectric layer was a layer of Al2O3. The thickness T1 of the first dielectric layer and the thickness T2 of the second dielectric layer obtained by the method described above were 10 nm and 3 nm, respectively, and T1 / T2 was 3.3. Since the second dielectric layer was formed by the ALD method, the variation in the measured thickness of the second dielectric layer at 10 points was small, with a standard deviation of 0.2 nm. The first metal was Al, the chemical conversion rate R was 2.0 nm / V (hereinafter referred to as product), and (T1 / R) / Vw was 2.5.

[0062] (Preparation of cathode foil) An Al foil having a thickness of 50 μm was subjected to an etching treatment to roughen the surface of the Al foil to obtain a cathode foil, which was then cut to a predetermined size.

[0063] (Making of the wound body) An anode lead tab and a cathode lead tab were connected to the anode foil and the cathode foil, and the anode foil and the cathode foil were wound with the lead tabs interposed between them. An anode lead wire and a cathode lead wire were connected to the ends of the lead tabs protruding from the wound body, respectively. Then, the wound body was subjected to a chemical conversion treatment again, and a dielectric layer was formed on the cut ends of the anode foil. Next, the ends of the outer surface of the wound body were fixed with a stop tape.

[0064] (Preparation of Conductive Polymer Dispersion) A mixed solution was prepared by dissolving 3,4-ethylenedioxythiophene and polystyrenesulfonic acid as a dopant in ion-exchanged water. While stirring the resulting mixed solution, iron (III) sulfate (oxidant) dissolved in ion-exchanged water was added to carry out a polymerization reaction. After the reaction, the resulting reaction solution was dialyzed to remove unreacted monomers and excess oxidant, and a conductive polymer dispersion containing polyethylenedioxythiophene doped with approximately 5% by mass of polystyrenesulfonic acid was obtained.

[0065] (Formation of solid electrolyte layer) The wound body was immersed in the conductive polymer dispersion liquid contained in a specified container in a reduced pressure atmosphere (40 kPa) for 5 minutes, and then the wound body was pulled out from the conductive polymer dispersion liquid. Next, the wound body impregnated with the conductive polymer dispersion liquid was dried in a drying furnace at 150°C for 20 minutes, and a solid electrolyte layer containing a conductive polymer was formed between the anode foil and the cathode foil.

[0066] (Sealing of the winding body) The wound body having the solid electrolyte layer was sealed to complete the electrolytic capacitor shown in Fig. 3. Thereafter, an aging treatment was performed at 130°C for 2 hours while applying the rated voltage Vw.

[0067] [evaluation] The electrostatic capacitance of the obtained electrolytic capacitor was measured. In addition, a voltage was applied while increasing at a rate of 1.0 V / sec, and a breakdown voltage at which an overcurrent of 0.5 A flows was measured. The electrostatic capacitance was expressed as an index (capacitance index C) with the electrostatic capacitance of the electrolytic capacitor of Comparative Example 3 taken as 100. The breakdown voltage was expressed as an index (voltage index V) with the breakdown voltage of the electrolytic capacitor of Comparative Example 3 taken as 100.

[0068] Examples 2 to 4 and Comparative Examples 1 to 2 Electrolytic capacitors were produced and evaluated in the same manner as in Example 1, except that the thickness T2 of the second dielectric layer was set to the value shown in Table 1. The thickness T2 of the second dielectric layer was controlled by changing the number of cycles of the ALD method.

[0069] Comparative Example 3 An electrolytic capacitor was produced and evaluated in the same manner as in Example 1, except that the second dielectric layer was not formed.

[0070] Examples 5 and 6 Electrolytic capacitors were fabricated and evaluated in the same manner as in Example 1, except that the thickness T1 of the first dielectric layer and the thickness T2 of the second dielectric layer were set to the values ​​shown in Table 1. The thickness T1 of the first dielectric layer was controlled by changing the chemical formation voltage Vf. The thickness T2 of the second dielectric layer was controlled by changing the number of cycles of the ALD method.

[0071] The evaluation results of the electrolytic capacitors of Examples 1 to 6 and Comparative Examples 1 to 3 are shown in Table 1. The CV value is calculated by multiplying the capacitance by the breakdown voltage, and indicates the amount of electricity that the electrolytic capacitor can store. In Table 1, the CV value is expressed as an index (CV index) with the CV value of Comparative Example 3 set to 100.

[0072] [Table 1]

[0073] The electrolytic capacitors of Examples 1 to 6, in which the second dielectric layer was formed, had improved voltage resistance compared to the electrolytic capacitor of Comparative Example 3, in which the second dielectric layer was not formed. The electrolytic capacitors of Examples 1 to 6, in which T1 / T2 was greater than 1, had a good balance between excellent voltage resistance and good capacitance, and had a higher CV value than the electrolytic capacitor of Comparative Example 3. The electrolytic capacitors of Examples 1 to 3 and 5 to 6, in which T1 / T2 was greater than 1 and not greater than 20, exhibited improved voltage resistance and larger CV values. Among them, the electrolytic capacitors of Examples 5 to 6, in which the total thickness of T1 and T2 was small, exhibited larger capacitance and further increased CV values.

[0074] In the electrolytic capacitors of Comparative Examples 1 and 2, in which T1 / T2 was 1 or less, the capacitance decreased and the CV value was smaller than that of the electrolytic capacitor of Comparative Example 3.

[0075] Example 7 An electrolytic capacitor was fabricated and evaluated in the same manner as in Example 1, except that the thickness T1 of the first dielectric layer was set to 5 nm. The thickness T1 of the first dielectric layer was controlled by changing the chemical formation voltage Vf. EDX analysis confirmed that the second dielectric layer was a layer of SiO2.

[0076] Example 8 In the preparation of the electrode foil, an electrolytic capacitor was prepared and evaluated in the same manner as in Example 1, except that tetrakis(dimethylamino)zirconium(IV) was used as the precursor in the ALD method. EDX analysis confirmed that the second dielectric layer was a ZrO2 layer.

[0077] Example 9 In the production of electrode foil, tetrakis(III) is used as a precursor for the ALD method. ( Dimethylamino ) Except for using hafnium, an electrolytic capacitor was fabricated and evaluated in the same manner as in Example 1. EDX analysis confirmed that the second dielectric layer was a layer of HfO2.

[0078] Example 10 In the preparation of the electrode foil, pentakis(dimethylamino)tantalum(V) was used as the precursor in the ALD method, but an electrolytic capacitor was prepared and evaluated in the same manner as in Example 1. EDX analysis confirmed that the second dielectric layer was a layer of Ta2O5.

[0079] The evaluation results of the electrolytic capacitors of Examples 7 to 10 are shown in Table 2.

[0080] [Table 2]

[0081] In all of the examples, electrolytic capacitors with large capacitance and excellent voltage resistance were obtained. When the second metal oxide was SiO2, a thin and dense second dielectric layer was formed, and the voltage resistance was further improved. When the second metal oxide was HfO2, the capacitance was further improved. [Industrial Applicability]

[0082] The electrode foil according to the present invention can be used in capacitors for various applications because it improves capacitance and voltage resistance. [Explanation of symbols]

[0083] 10: anode foil, 110: anode body, 111: core, 112: porous portion, 120: dielectric layer, 121: first dielectric layer, 122: second dielectric layer, P: pit, 20: cathode foil, 30: separator, 40: stop tape, 60A, 60B: lead wire, 50A, 50B: lead tab, 100: wound body, 200: electrolytic capacitor, 211: bottomed case, 212: sealing member, 213: seat plate

Claims

1. an anode body including a first metal; a first dielectric layer covering at least a portion of the anode body and including an oxide of the first metal; a second dielectric layer covering at least a portion of the first dielectric layer and including an oxide of a second metal different from the first metal; the first metal is aluminum; the second metal is silicon; a ratio (T1 / T2) of a thickness T1 of the first dielectric layer to a thickness T2 of the second dielectric layer is 1.3 or more and 20 or less; The electrode foil for an electrolytic capacitor, wherein a total thickness of the first dielectric layer (T1) and the second dielectric layer (T2) is 12.5 nm or less.

2. The electrode foil according to claim 1 ; a solid electrolyte layer covering at least a portion of the second dielectric layer of the electrode foil; The solid electrolyte layer comprises a conductive polymer.

3. The electrolytic capacitor of claim 2 , further comprising a solvent or an electrolyte.

4. the first dielectric layer is a conversion coating; 4. The electrolytic capacitor according to claim 2, wherein a ratio T1 / R of a thickness T1 (nm) of the first dielectric layer to a chemical conversion rate R (nm / V) of the chemical conversion coating, and a rated voltage Vw (V) of the electrolytic capacitor satisfy a relationship of (T1 / R) / Vw≦3.

5. A first step of chemically converting a substrate containing a first metal to form a first dielectric layer containing an oxide of the first metal so as to cover at least a portion of the substrate; a second step of forming a second dielectric layer, the second dielectric layer including an oxide of a second metal different from the first metal, and having a thickness T2 smaller than a thickness T1 of the first dielectric layer, so as to cover at least a portion of the first dielectric layer, to obtain an electrode foil; the first metal is aluminum; the second metal is silicon; a ratio (T1 / T2) of a thickness T1 of the first dielectric layer to a thickness T2 of the second dielectric layer is 1.3 or more and 20 or less; A method for manufacturing an electrolytic capacitor, wherein a total thickness of the first dielectric layer (T1) and the second dielectric layer (T2) is 12.5 nm or less.

6. 6. The method for producing an electrolytic capacitor according to claim 5, wherein in the second step, the second dielectric layer is formed by atomic layer deposition.

7. In the first step, a chemical conversion voltage Vf is applied to the substrate, 7. The method for producing an electrolytic capacitor according to claim 5, wherein a ratio of the formation voltage Vf to a rated voltage Vw of the electrolytic capacitor: Vf / Vw is 3 or less.

8. The method for producing an electrolytic capacitor according to any one of claims 5 to 7, further comprising a third step of forming a solid electrolyte layer containing a conductive polymer so as to cover at least a portion of the second dielectric layer of the electrode foil.

9. The method for producing an electrolytic capacitor according to claim 8 , further comprising the step of impregnating the electrode foil with a solvent or an electrolyte after the third step.

Citation Information

Patent Citations

  • Electrode foil, electrolytic capacitor and manufacturing method of electrode foil

    JP2015115475A

  • Method for producing electrode foil and method for manufacturing electrolytic capacitor

    WO2017154461A1

  • Electrode, electrolytic capacitor, and method for manufacturing those

    WO2018180029A1